Монголын залуучуудын хөдөлгөөний түүхийн асуудалд - Болдбаатар, Жигжид (Historia Mongolarum, 2003)
To the issue of Mоngolian Youth movemet. The foundation for Mongolian youth movement was established in 1921, 25th August with creation of Mongolian Revolutionary Youth League. In 1920’s, youth organization sought to challenge the pulling MPRR . In the peril of 1930-1990, MRYL became the assistant vestures of MPRP and contributed a lot to the building new society. Since 1990 in reformation times MVO heard.